Persistent allopeptide reactivity and epitope spreading in chronic rejection of organ allografts. - Ciubotariu, R (1998)
The role of the indirect allorecognition pathway in acute allograft rejection has been documented both in organ recipients and in experimental models. However, it is unknown whether self-restricted recognition of donor alloantigens also contributes to chronic allograft rejection. The aim of this study was to determine the relationship between allopeptide reactivity, epitope spreading, and chronic rejection. Using synthetic peptides corresponding to the hypervariable region of 32 HLA-DR alleles, we have followed the specificity of self-restricted T cell alloresponses to the donor in a population of 34 heart allograft recipients. T cells from sequential samples of blood collected from the patients up to 36 mo after transplantation were studied in limiting dilution analysis for allopeptide reactivity. The incidence of coronary artery vasculopathy (CAV) was significantly higher in patients who displayed persistent alloreactivity late after transplantation than in patients who showed no alloreactivity after the first 6 mo after transplantation. Both intra- and intermolecular spreading of epitopes was observed with an increased frequency in patients developing CAV in less than 2 yr, compared with patients without CAV; this suggests that diversification of the immune response against the graft contributes to chronic rejection. These data provide a strategy for identifying patients at risk of developing CAV and a rationale for therapeutic intervention aimed to prevent the progression of the rejection process.